2018
DOI: 10.1021/acscatal.8b03201
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Crucial Role of Single Active Water Molecule in the Oxidative Cleavage of Aliphatic C–C Bond of 2,4′-Dihydroxyacetophenone Catalyzed by 2,4′-Dihydroxyacetophenone Dioxygenase Enzyme: A Quantum Mechanics/Molecular Mechanics Investigation

Abstract: 2,4′-Dihydroxyacetophenone dioxygenase (DAD), a nonheme dioxygenase enzyme, shows exquisite selectivity in the aliphatic C–C bond cleavage of 2,4′-dihydroxyacetophenone (DHAP) in the presence of molecular oxygen (O2). Molecular dynamics simulations revealed the presence of a single water molecule at the active site of the enzyme. This lone water molecule is pivotal for facilitating the oxidative cleavage of the aliphatic C–C bond of 2,4′-DHAP catalyzed by DAD enzyme, as evident from the findings of our hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 68 publications
3
22
0
1
Order By: Relevance
“…The Fe-O distance has elongated to 1.796 Å and the axial Fe-N bond to 2.204 Å. These changes mimic previous calculations on analogous reaction mechanisms well [26][27][28][29][30][31][32][33][34][35][36]. The transition state has a modest imaginary frequency of i619 cm −1 , which is well lower than typical hydrogen atom abstraction transition states that usually have values well over i1000 cm −1 [72][73].…”
Section: Substrate Desaturation Via Pathways 1 Andsupporting
confidence: 76%
See 1 more Smart Citation
“…The Fe-O distance has elongated to 1.796 Å and the axial Fe-N bond to 2.204 Å. These changes mimic previous calculations on analogous reaction mechanisms well [26][27][28][29][30][31][32][33][34][35][36]. The transition state has a modest imaginary frequency of i619 cm −1 , which is well lower than typical hydrogen atom abstraction transition states that usually have values well over i1000 cm −1 [72][73].…”
Section: Substrate Desaturation Via Pathways 1 Andsupporting
confidence: 76%
“…For cysteine dioxygenase a combination of UV-Vis absorption and electron paramagnetic resonance studies implicated a short-lived oxygen-bound intermediate, which was tentatively identified as either the iron(III)-superoxo species or the bicyclic ring structure [24]. Many computational studies investigated the structure and properties of the iron(IV)-oxo species of nonheme iron dioxygenases in detail using either density functional theory model complexes or quantum mechanics/molecular mechanics methods [25][26][27][28][29][30][31][32][33][34][35][36]. These studies identified the iron(IV)-oxo as a quintet spin ground state showed it to be an efficient oxidant of substrate hydroxylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the oxo rotation is a continuous process in the decarboxylation starting from the Fe(III)-OO The change in the free energy of the reaction ∆Gr from IM2 to IM4 is associated with a value of -41.1 kcal/mol, indicating the overall decarboxylation reaction process is significantly exergonic ( Figure 2H), which is consistent with previous studies on non-heme iron αKG dependent enzymes 6,40 . The IM4 exhibits a 5C trigonal bipyramid geometry, consistent with the results The dominant spin states of iron in non-heme enzymes remains a long controversy 40,43,44, 64-66 , although quintet state has recently been suggested to be the ground state for the resting state and the Fe (IV)=O intermediate in other non-heme enzymes 45,46,55,56,57 , Since the ground state may change along the sequential reaction steps, here we calculated the different spin states (namely, triplet, quintet and septet spin states) of all the species involved in the decarboxylation process using QM/MM optimization. It is shown that the quintet state is consistently the ground state for all the species in the reaction process (Table S2).…”
Section: Formation Of Fe(iv)=o From Peroxo-bridged Intermediatesupporting
confidence: 83%
“…Optimized geometries of the triplet and quintet spin reactant complexes ( 3,5 Re) are shown in Figure 2. Similarly to previous computational studies on analogous iron(IV)-oxo complexes of nonheme iron enzymes [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and experimental EPR and Mössbauer measurements of related nonheme iron dioxygenases, 30,31,[85][86][87] the quintet spin state is the ground state. Because of this molecular orbital occupation, the Fe-O distance is short in 5 Re, i.e.…”
Section: Methodsmentioning
confidence: 80%